6(x-2)(3-(4x-5))=3x-(6x-5)

Simple and best practice solution for 6(x-2)(3-(4x-5))=3x-(6x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-2)(3-(4x-5))=3x-(6x-5) equation:



6(x-2)(3-(4x-5))=3x-(6x-5)
We move all terms to the left:
6(x-2)(3-(4x-5))-(3x-(6x-5))=0
We calculate terms in parentheses: -(3x-(6x-5)), so:
3x-(6x-5)
We get rid of parentheses
3x-6x+5
We add all the numbers together, and all the variables
-3x+5
Back to the equation:
-(-3x+5)
We get rid of parentheses
6(x-2)(3-(4x-5))+3x-5=0
We add all the numbers together, and all the variables
3x+6(x-2)(3-(4x-5))-5=0
We move all terms containing x to the left, all other terms to the right
3x+6(x-2)(3-(4x-5))=5

See similar equations:

| 1/8/1/3×2=x | | 1/8÷1/3×2=x | | 16x^2+12x=-18 | | 16x^2+12x+18=0 | | (5/4a-2)-1=4/5 | | 3x+4=2×+2 | | 1/8x+1=-8 | | (U-5)/(u^2-36)=0 | | 3x+1=13-× | | 1+7x=6x+5 | | 0.7x+0.4=0.9x-0.6 | | (y-4)(y-3)=-2 | | 7+x=2x+5 | | 8x+3.5=7x+2 | | 21=+6x-9 | | 14p-6p+42=p+9 | | 7(4x+8)+9(4x+8)+3=64+132 | | 0.4=0.32/y | | 7(2a-4)=(a+4) | | 98=(2*98/h)*h | | x+4.3=9.9 | | -16=x/6 | | 3(x+2)=7(9x-6)+10 | | 4(x-1)=4x+1 | | A=(2A/h)*h | | 4(x+1)=4x-1 | | 20=5x-1 | | -(3x-(2x+5))=-4-(3(2x-4)-3x | | -(3x0(2x+5))=-4-(3(2x-4)-3x | | b−316=516. | | 1+19=-4(5x-5) | | 4.7x=5.17 |

Equations solver categories